Analisis Penerimaan Dana Kredit Usaha Rakyat (KUR) Pada UMKM pada PT. Bank BRI Unit Tapa Kota Gorontalo - Gita Damyanti; Zulkifli Bokiu; Ronald S. Badu (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to find out whether there is an impact on providing people's business credit (KUR) to MSMEs at PT. Bank Rakyat Indonesia (Persero) Tbk. Tapa Unit Gorontalo Branch Office. This research uses qualitative methods with the data sources used, namely primary and secondary data. The data collection techniques used were observation, interviews and documentation. The object of this research is an analysis of the provision of people's business credit (KUR) funds to PT. BRI bank unit tapa Gorontalo city. The results of the research show that there is an assessment of the character of prospective customers at Bank BRI Tapa unit which is intended to determine the candidate's honesty and good faith in paying off or returning the loan, so that it will not cause difficulties for the bank in the future. The relationship between credit giver and credit recipient is a mutually beneficial cooperative relationship with the credit giver's trust in the credit recipient based on the credit recipient's credit rating. The procedures for granting and assessing credit by the banking world between the BRI Tapa unit and other banks are not much different. The difference may only lie in the procedures and requirements established with individual considerations. Settlement of bad debts in KUR credit at Bank BRI Unit cannot be resolved non-litigationally because Kur itself is a program from the government to make it easier for people who want to do business.